Workplace interpersonal conflicts among healthcare professionals: A survey on conflict solution approach at a General Hospital - Saridi, Maria; Panagiotidou, Athina; Toska, Aikaterini; Panagiotidou, Maria; Sarafis, Pavlos (My University, 2021)
We investigated the factors that shape the working environment and workload, as these are reflected by the presence of conflicts among employees of a General Hospital in Greece. A cross-sectional study was conducted using a 20-part questionnaire, which was administered to 200 health care professionals. 24,5% of the participants referred that they want to quit their profession soon and nurses showed the majority and the doctors the lowest percentage (60%vs 7%). The willingness to change the working environment did not appear to depend on gender, marital status, work position and work schedule. The majority of the respondents reported that conflicts occur at their workplace, with the medical staff showing the greatest average number of conflicts in relation to both the other two professional groups. In particular, it was found that those who did not have a managerial position were 3.9 times more likely to choose to compromise in a conflict.
Keywords: Conflict management; Healthcare professionals; Hospitals; Managerial strategies; Nurses; Workplace conflicts